The Impact of Covid-19 Pandemic on Poverty in the Socio-Economic Field - Nabila Marsa Faudiana (Journal of Islamic Economic Scholar, 2021)
The Covid-19 (Coronavirus) pandemic is a virus that causes disease in humans and animals. The virus that has spread since the beginning of 2020 more or less in March, all residents are shocked by this Covid-19 Pandemic. The COVID-19 pandemic has changed everything, from lifestyle and caused a lot of losses for everyone. This study aims to determine the impact of Covid-19 on Poverty in Tirto, Pekalongan. The research method used is qualitative research and library studies to support this research. From the results of research that has been carried out, the impact of Covid-19 is very large. Everything changes and there is not a single person who is not harmed by this Pandemic. Starting from rich entrepreneurs, employees, traders, even online motorcycle taxi drivers. Covid-19 makes everyone have to be able to rack their brains to think how to survive during this Pandemic. However, on the other hand, the government participates in assisting the community in tackling poverty by providing social assistance. Such as providing subsidy funds for Micro, Small and Medium Enterprises (MSMEs) through BRI bank.